Predictors of Release from Guantánamo Bay and Detainee Recidivism1 - Fahey, Susan (International Journal of Criminology and Sociology, 2013)
Exploring Reports of Recidivism by Guantánamo Bay Releasees. The purpose of this research is to examine what is known about recidivism by Guantánamo Bay releasees. Government reports suggest that approximately 27 percent of these releasees have returned to the battlefield while reporting in the open source media identifies the recidivism rate as nearly 9 percent. Deterrence, labeling and defiance theories were applied to explain their recidivism, and The New York Times’ Guantánamo Docket document release was used to code the 779 detainees on whether they were released, their nationality, age, time since release, risk level, intelligence value and other relevant domains. The recidivism data were obtained from the New America Foundation. These datasets were used to model the predictors of release from Guantánamo Bay and the predictors of recidivism for those who were released. Risk level, intelligence value, membership in multiple groups, and being of Yemeni nationality all statistically significantly affected the likelihood of release. However, only time since release predicted recidivism. It is likely that the proportion of detainees identified as recidivists will increase over time, as time to offend and be discovered increases, and as higher-risk detainees are released as part of the Obama Administration’s attempts to empty the island prison.